2016
DOI: 10.1111/infa.12171
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Toddlers' Naturalistic Media Experience and Observed Learning from Screens

Abstract: Using secondary analysis, researchers examined associations between two‐year‐olds' (N = 135) naturalistic use of interactive and noninteractive media with performance on a screen‐based learning task. Parents reported the number of minutes that children spent the previous day doing nine media‐related activities (e.g., watching television, playing handheld videogames). The object‐retrieval task required children to watch a hiding event on video and then search for the object on another screen or a real felt boar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 9 publications
(22 reference statements)
0
15
0
Order By: Relevance
“…This was not an ownership-related SRE paradigm, but does suggest that the children could get a sense of an association between themselves and a number of objects separate to another character presented on a screen. Children as young as two demonstrate comprehension from video screens ( Pempek et al, 2010 ), and can also make use of information presented to them on screens ( Troseth, 2003 ), particularly when there is interaction involved ( Troseth et al, 2006 ; Kirkorian and Choi, 2017 ). Krcmar and Cingel (2017) found that toddlers learned novel words via video better if the speaker spoke directly to the child and encouraged a response as opposed to when watching from a third person perspective.…”
Section: Discussionmentioning
confidence: 99%
“…This was not an ownership-related SRE paradigm, but does suggest that the children could get a sense of an association between themselves and a number of objects separate to another character presented on a screen. Children as young as two demonstrate comprehension from video screens ( Pempek et al, 2010 ), and can also make use of information presented to them on screens ( Troseth, 2003 ), particularly when there is interaction involved ( Troseth et al, 2006 ; Kirkorian and Choi, 2017 ). Krcmar and Cingel (2017) found that toddlers learned novel words via video better if the speaker spoke directly to the child and encouraged a response as opposed to when watching from a third person perspective.…”
Section: Discussionmentioning
confidence: 99%
“…A final complementary explanation for age‐related change in transfer has to do with children's prior experience with different types of media. The amount of time toddlers watch television and videos at home does not predict how well they do on video‐based learning tasks in a laboratory setting; however, toddlers' naturalistic experience with interactive media such as video chats and digital games does predict performance on video‐based learning tasks . This correlational finding was replicated in an experimental study in which some 2‐year‐olds were assigned randomly to several weeks of training with a live video feed (i.e., seeing themselves on their home television set) before coming to the laboratory to complete an object retrieval task .…”
Section: Who Is Most Likely To Benefit From Interactivity?mentioning
confidence: 98%
“…This correlational finding was replicated in an experimental study in which some 2-yearolds were assigned randomly to several weeks of training with a live video feed (i.e., seeing themselves on their home television set) before coming to the laboratory to complete an object retrieval task (38). This type of actual experience with symbolic media may help children recognize the symbolic nature of video screens (27), enabling them to succeed on learning tasks that use symbolic media such as photographs, videos, and touchscreen applications (36,37).…”
Section: Who Is Most Likely To Benefit From Interactivity?mentioning
confidence: 99%
“…The majority of the established research on the effects of interactive digital media on infants, toddlers, and preschoolers has focused on games and apps designed to strengthen preliteracy and literacy skills (e.g., Dore et al., ; Kirkorian & Choi, ). However, researchers have shown increasing interest in examining children's development of STEM (science, technology, engineering, and mathematics) skills in the context of app play.…”
Section: Media Use Among Young Childrenmentioning
confidence: 99%